Envision "Disability": "Abnormal People" and "The Wizards" in Early Ancient Times - Shengping Li (Wolters Kluwer Health/LWW, 2020)
As a natural phenomenon, people with disabilities were not stigmatized from the very beginning. In antiquity, some parts of their body being "different from those of normal persons," they were considered to have a special ability to communicate with heaven, earth, and the Gods. As a result, people with disabilities were able to hold the position of "wizard," which had a high status and important influence. However, with the division of labor in the human society, people with disabilities gradually lost the prerogative in labor production due to the limitation of their ability to work, which affected their social status and led to the social discrimination and "stigmatization" toward them gradually. Before this transformation happened, people's envision on people with disabilities, including a variety of images, was indicative of the social consciousness at that time.